Pengaruh Media Pembelajaran Historical Dominoes (HD) untuk Meningkatkan Hasil Belajar Sejarah Siswa - Putri Chairini*; Husaini Ibrahim; Muhjam Kamza (Universitas Syiah Kuala, 2023)
This study aims to determine the increasement in student history learning outcomes before the application of historical domino media and after the application of historical domino media at SMA Negeri 12 Banda Aceh. This study used a quantitative approach and the type of experimental research. The population in this study was all students. Based on the results of data processing using the IBM SPSS Statistics 20 application with the formula of Shapiro Wilk, it was obtained that the significance value Sig.(2-tailed) of the pretest was worth 0,00 and the significance value Sig.(2-tailed) of the posttest was 0,021, where both values is under the value of (α) = 0.05. Thus, H_0 is rejected and H_1 is accepted, so that, the distribution of the pretest and post-test data is not normally distributed so the average difference test will be carried out using the Wilcoxon formula. The value of Sig.(2-tailed) in the Wilcoxon test is 0.01 which is greater than the value (α) = 0.05.